(untitled) (MSW Management Journal, 2026)
This study analysis the evolution of academic research on Government spending on social sectors in India during the post-reform period (1991–2024) using a bibliometric approach based on Scopus-indexed publications. The analysis evaluates annual publication growth, authorship patterns, institutional contributions, country collaboration networks, citation performance, and thematic keyword structures. The findings reveal a steady increase in research output, with significant expansion after the mid-2000s, coinciding with the implementation of major welfare programmes and greater emphasis on inclusive development. Thematic analysis indicates that the literature is organized around three major domains: fiscal management, development outcomes, and governance structures. Keywords such as income inequality, public expenditure, federalism, and social programmes highlight the integration of fiscal policy with human development concerns. Authorship and institutional patterns suggest a decentralized research structure with moderate international participation. The results shows that Government spending on social sectorshas emerged as a central area of inquiry within public finance and development economics. The study contributes by mapping the intellectual structure and research trajectory of this field, providing insights into emerging themes and potential directions for future research.